The Impact of Uncertainty Reporting on the Loan Decision - Libby, Robert (Journal of Accounting Research, 1979)
Robert Libby, The Impact of Uncertainty Reporting on the Loan Decision, Journal of Accounting Research, Vol. 17, Studies on Auditing-Selections from the "Research Opportunities in Auditing" Program (1979), pp. 35-57